CFD simulation study on the performance of a modified Ram Air Turbine (RAT) for power generation in aircrafts - M. Saad, Magedi Moh; Mohd, Sofian; Zulkafli, Mohd Fadhli; Samiran, Nor Afzanizam; Didane, Djamal Hissein
The present paper aims to study the possibility of dispensing an auxiliary power unit (APU) in an aircraft powered by fossil fuels to reduce air pollution. It particularly seeks to evaluate the amount of power generated by the ram air turbine (RAT) using the novel counter-rotating technique while characterizing its optimum axial distance. The ram air turbine (RAT), which is already equipped in aircrafts, was enhanced to generate the amount of energy produced by the APU. The approach was implemented by a CRRAT system. Six airfoil profiles were tested based on 2D models and the best airfoil was chosen for implantation on the RAT and CRRAT systems. The performance of the conventional single-rotor RAT and CRRAT were analyzed using FLUENT software based on 3D models. The adopted numerical scheme was the Navier–Stokes equation with k–ω SST turbulence modeling. The dynamic mesh and user-defined function (UDF) were used to revolve the rotor turbine via wind. The results indicated that the FX63-137 airfoil profile showed a higher performance in terms of the lift-to-drag ratio compared to the other airfoils. The optimum axial distance between the two rotors was 0.087 m of the rotor diameter and the efficiency of the new CRRAT increased to almost 45% compared to the single-rotor RAT.